Effect of alkaline extraction pH on structure properties, solubility, and beany flavor of yellow pea protein isolate. (May 2020) - Gao, Zili; Shen, Peiyi; Lan, Yang; Cui, Leqi; Ohm, Jae-Bom; Chen, Bingcan; Rao, Jiajia
Graphical abstract: Highlights: The yield, functionality and beany flavor of pea protein was affected by extraction pH. The protein aggregates and extraction yield increased as the pH increased. The percentage solubility of yellow pea isolate decreased with increasing extraction pH. Pea protein extracted at pH 9.0 possessed the lowest beany flavors. The lowest lipoxygenase activity was found in pea protein isolate obtained at pH 9. Abstract: In the current study, the impact of alkaline extraction pH (8.5, 9.0, and 9.5) on chemical composition, molecular structure, solubility and aromatic profile of PPI was investigated by sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE), the quantification of free sulfhydryl group and disulfide bond contents, size exclusion chromatography with multi-angle static light scattering and refractive index (SEC-MALS-RI), circular dichroism (CD) spectroscopy, and headspace solid phase micro extraction gas chromatography-mass spectroscopy (HS-SPME-GC–MS). We found that protein recovery yield increased from 49.20% to 57.56% as the alkaline extraction pH increased from 8.5 to 9.5. However, increasing the extraction pH promoted the formation of protein aggregates which decreased the percent protein solubility although there was no influence on protein secondary structure. PPI extracted at pH 9.0 possessed the lowest beany flavor as revealed by the selected six beany flavor markers including alcohols, aldehydes, ketones and pyrazine. The lowest lipoxygenase activity at pH 9.0 may contribute to the least beany flavor in PPI. Therefore, pH 9.0 was found to be the optimal condition for preparing premium PPI in terms of yield, functionality, and aromatic profile using alkaline extraction-isoelectric precipitation process. The findings could have fundamental implications for the preparation and utilization of pea proteins in food applications.